Involuntary Neuromuscular Coupling between the Thumb and Finger of Stroke Survivors during Dynamic Movement - Jones, Christopher L.; Kamper, Derek G. (Frontiers in Neurology, 2018)
Finger-thumb coordination is crucial to manual dexterity but remains incompletely understood, particularly following neurological injury such as stroke. While being controlled independently, the index finger and thumb especially must work in concert to perform a variety of tasks requiring lateral or palmar pinch. The impact of stroke on this functionally critical sensorimotor control during dynamic tasks has been largely unexplored. In this study, we explored finger-thumb coupling during close-open pinching motions in stroke survivors with chronic hemiparesis. Two types of perturbations were applied randomly to the index with a novel cable-actuated finger exoskeleton: a sudden joint acceleration stretching muscle groups of the index finger and a sudden increase in impedance in selected index finger joint(s). Electromyographic signals for specific thumb and index finger muscles, thumb tip trajectory, and index finger joint angles were recorded during each trial. Joint angle perturbations invoked reflex responses in the FDS, FDI, and EDC muscles of the index finger and heteronymous reflex responses in FPB of the thumb (p<0.017). Phase of movement played a role as a faster peak reflex response was observed in FDI during opening than during closing (p<0.002) and direction of perturbations resulted in shorter reflex times for FDS and FDI (p<0.012) for extension perturbations. Surprisingly, when index finger joint impedance was suddenly increased, thumb-tip movement was substantially increased, maintaining aperture and increasing movement from 2 cm to 10 cm (p<0.001). A greater effect was seen during the opening phase (p<0.044). Thus, involuntary finger-thumb coupling was present during dynamic movement, with perturbation of the index finger impacting thumb activity. The degree of coupling modulated with the phase of motion. These findings reveal a potential mechanism for direct intervention to improve post-stroke hand mobility, and provides insight on prospective neurologically oriented therapies.